GENDER IDENTITY DISORDER. IS THIS A POTENTIALLY FATAL CONDITION? - Yousafzai, Abdul Wahab; Bhutto, Naila (Journal of Ayub Medical College Abbottabad, 2007)
A person with a Gender Identity Disorder (GID) is a person who strongly identifies with the other sex. The individual may identify with the opposite sex to the point of believing that he/she is, in fact, a member of the other sex who is trapped in the wrong body. The treatment option is sex reassignment surgery. In Pakistan There is no specialized facility sex reassignment surgery. This case report deals with possible serious outcome of GID in Pakistan as a result of castration procedure which is carried out by '˜gurus' in Pakistan. A systemic research in our country to this effect is required to find out the outcome of GID in Pakistan. Keywords: Gender Identity Disorder; Castration; Sex Reassignment Surgery.